Microalgal biomass generation by phycoremediation of dairy industry wastewater: An integrated approach towards sustainable biofuel production. (December 2016) - Chokshi, Kaumeel; Pancha, Imran; Ghosh, Arup; Mishra, Sandhya
Highlights: Acutodesmus dimorphus was grown in raw dairy wastewater without any dilution. Biomass production increased by 5–6 folds in dairy wastewater compared to control. A. dimorphus produced 25% lipid and 30% carbohydrate when grown in dairy wastewater. 273 g of biofuel can be produced from 1 kg dry biomass of A. dimorphus. Abstract: Dairy wastewater collected from local dairy industry was used as a growth media (without any pre-treatment) for the cultivation of microalgae Acutodesmus dimorphus . The level of COD reduced over 90% (from 2593.33 ± 277.37 to 215 ± 7.07 mg/L) after 4 days of cultivation; whereas, ammoniacal nitrogen was consumed completely (277.4 ± 10.75 mg/L) after 6 days of cultivation. Dry biomass of 840 and 790 mg/L was observed after 4 and 8 days of cultivation, respectively, which is about 5–6 times more than that of BG-11 grown culture (149 mg/L after 8 days). This biomass contains around 25% lipid and 30% carbohydrate, which can be further converted into biodiesel and bioethanol, respectively. Theoretical calculations based on the recently reported conversion yield suggest that 1 kg biomass of A. dimorphus might produce around 195 g of biodiesel and 78 g of bioethanol, which sums up to 273 g of biofuels.